Reduced Survival in Patients with “Coronary Microvascular Disease” - Lin, Terence; Rechenmacher, Stephen; Rasool, Shuja; Varadarajan, Padmini; Pai, Ramdas G. (International Journal of Angiology, 2012)
The syndrome of chest pain, abnormal stress test, and nonflow limiting coronary artery disease (CAD) is common and is attributed to coronary microvascular disease (µVD). It is associated with increased hospital admissions and health care costs. But its impact on long-term survival is not known. Of the 9941 consecutive patients who had an exercise stress test for evaluation of chest pain between May 1991 and July 2007, 935 had both a positive stress test and a coronary angiogram within 1 year of their stress test forming the study cohort. Significant angiographic CAD defined as ≥70% stenosis of an epicardial coronary artery or ≥50% stenosis of the left main coronary artery was present in 324 patients. Rest (n = 611) were considered to have coronary µVD. Compared with patients with significant epicardial CAD, patients with coronary µVD were younger (63 ± 11 vs. 65 ± 10 years, p = 0.002), and had lower left ventricular wall thickness (p < 0.02), systolic blood pressure (BP; p = 0.002), pulse pressure (0.0008), systolic BP with exercise (p = 0.0001), and pulse pressure with exercise (p < 0.0001). Those with coronary µVD had a better survival compared with those with significant epicardial CAD, but worse than that expected for age- and gender-matched population (p < 0.0001). Coronary µVD as a cause of chest pain and positive stress test is common. All-cause mortality in patients with coronary µVD is worse than in an age- and gender-matched population control, but better than those with significant epicardial CAD.
Keywords: chest pain; coronary artery disease; microvascular disease; survival; prognosis